2006
DOI: 10.1097/01.mib.0000219350.72483.44
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Induce Neurotrophic Factor Expression in Enteric Glia

Abstract: A mucosal GFAP expressing EGC population is dramatically increased in CD. This population is a major cellular source of the upregulated GDNF in the inflamed gut. Therefore, mucosal EGC may play a key role in protecting the gut epithelium and may contribute to reestablish the integrity of the injured epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…All this confirms the leading role performed by the enteric glia in the inflammation and therefore it could be regarded as an important source of cytokines in the neuroimmune network of the intestine [1-5]. …”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…All this confirms the leading role performed by the enteric glia in the inflammation and therefore it could be regarded as an important source of cytokines in the neuroimmune network of the intestine [1-5]. …”
Section: Introductionmentioning
confidence: 61%
“…Therefore, changes in the nervous functions could represent an important link between inflammation and neurodegeneration, and this link could be represented by the glial cells, which have demonstrated to control the enteric neuronal functions [1-5]. In particular, alterations of the glial cells may be responsible of the increase of the mucosal barrier permeability, of the neuronal cells' proliferation and of the production of neurokines.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular and biochemical analysis as well as cell biology approaches demonstrated important regulatory functions of mucosal EGC in the assembly and maintenance of intestinal mucosa integrity [9,10]. This is underscored by the potential of EGC to secrete key cytokines and growth factors such as interleukin-6 (IL-6), and TGF-ß1 [15,16], which ensure cell communication with the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophins has been identified as antiapoptotic substances for the colonic epithelial cells [8,9]. The source of neurotrophins and neurotrophic factors could be identified as the enteric glia cells (EGC) of the mucosal plexus [10]. On the other hand, it was shown that in Crohn's disease (CD) the amount of glial cells is reduced [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…diabetic gastroparesis) (Thazhath et al, 2013), infection (achalasia and colon dysmotility in Chagas disease (Machado et al, 2012), varicella zoster (Chen et al, 2011; Holland-Cunz et al, 2006)), toxins (e.g., ethanol) (Krecsmarik et al, 2006), or local inflammation (causing inflammatory bowel disease associated dysmotility (Mawe, 2015; Mawe et al, 2009; Vasina et al, 2006) and post-infectious irritable bowel syndrome (Spiller and Garsed, 2009)). In part, post-inflammatory changes in the ENS may be mediated by cytokines that induce GDNF and NGF synthesis in enteric glia or alter glial phenotypes (von Boyen et al, 2006a; von Boyen et al, 2004, 2006b). Enteric glia modulate neuronal function to regulate motility, and can affect neuron survival and bowel epithelial barrier function, among other roles (Brown et al, 2016; Ochoa-Cortes et al, 2016; Sharkey, 2015).…”
Section: Non-hscr Motility Disordersmentioning
confidence: 99%